Barleria gandhii, a new name for Barleria pauciflora (Acanthaceae) - Kottaimuthu, Ramalingam (Phytotaxa, 2015)
Barleria Linnaeus (1753: 636) is a pantropical genus comprising about 250–300 species (Balkwill & Balkwill 1998, Darbyshire et al. 2012), with its greatest centre of species diversity in tropical Africa, followed by South Africa and Asia (Balkwill & Balkwill 1998, Darbyshire 2010). It can be easily distinguished from other genera of Acanthaceae by a combination of three characters: a 4-partite calyx with 2 large outer (anterior and posterior) segments and 2 smaller inner (lateral) ones, spheroidal, pollen grains with coarsely reticulate exine and the predominance of double cystoliths (calcium oxalate crystals) in the epidermal cells (Balkwill & Balkwill 1997, Champluvier 2011, Darbyshire 2010).